2009
DOI: 10.1097/jcp.0b013e3181a390ce
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of OROS Methylphenidate in Adults With Attention-Deficit/Hyperactivity Disorder

Abstract: In a dose escalation ranging from 36 to 108 mg/d, OROS methylphenidate is effective and well tolerated in the management of ADHD in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 44 publications
8
51
0
Order By: Relevance
“…ADHD medication has been shown to have advantageous short-term effects on ADHD symptoms (Adler, et al, 2009; Banaschewski, et al, 2006; Findling, 2008; Findling, et al, 2008; Koesters, et al, 2009; Kooij, et al, 2010; Newcorn, et al, 2008; Svanborg, et al, 2009; Young, et al, 2011), and, similar to a study on drug related criminality (Lichtenstein, et al, 2012), our data suggest a concomitant association between stimulant ADHD treatment and lower rates of substance abuse. Even though short-term effects might be beneficial, there has been a persistent concern that treatment with stimulant medication could lead to long-term development of substance abuse (Singh, 2008; Winhusen, et al, 2011), and our previous study did not explore long-term associations with drug abuse and only addressed drug related criminality (i.e., not deaths or hospitalizations, which were more common than convictions).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…ADHD medication has been shown to have advantageous short-term effects on ADHD symptoms (Adler, et al, 2009; Banaschewski, et al, 2006; Findling, 2008; Findling, et al, 2008; Koesters, et al, 2009; Kooij, et al, 2010; Newcorn, et al, 2008; Svanborg, et al, 2009; Young, et al, 2011), and, similar to a study on drug related criminality (Lichtenstein, et al, 2012), our data suggest a concomitant association between stimulant ADHD treatment and lower rates of substance abuse. Even though short-term effects might be beneficial, there has been a persistent concern that treatment with stimulant medication could lead to long-term development of substance abuse (Singh, 2008; Winhusen, et al, 2011), and our previous study did not explore long-term associations with drug abuse and only addressed drug related criminality (i.e., not deaths or hospitalizations, which were more common than convictions).…”
Section: Discussionsupporting
confidence: 84%
“…Randomized controlled studies suggest that ADHD medication have beneficial short-term effects on symptoms of ADHD (Adler et al, 2009; Banaschewski et al, 2006; Findling, 2008; Findling et al, 2008; Koesters, Becker, Kilian, Fegert, & Weinmann, 2009; Kooij et al, 2010; Newcorn et al, 2008; Svanborg et al, 2009; Young, Sarkis, Qiao, & Wietecha, 2011). This is supported by a recent large study indicating significant associations between ADHD medication and reductions in criminality while under treatment (Lichtenstein et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Our study findings are comparable with those reported by Adler et al using a flexible dose range of osmotic-release oral system (OROS) methylphenidate (36–108 mg/day), wherein adult ADHD patients initiating therapy at 36 mg/day with weekly increments of 18 mg/day showed good safety and tolerability outcomes [8, 9]. In their study, the protocol was designed to reach the minimal effective dose rather than optimizing the dose.…”
Section: Discussionsupporting
confidence: 89%
“…Methylphenidate (MPH) appears to be an effective and safe treatment in adults with ADHD in doses up to 1.3 mg/kg 68, but so far evidence is lacking on the efficacy of stimulant pharmacotherapy to treat comorbid ADHD and SUD. Several randomized clinical trials (RCT) of pharmacotherapy for ADHD in SUD, primarily cocaine dependence, have evaluated the utility of MPH in current users 911 and in recently abstinent users 12.…”
Section: Introductionmentioning
confidence: 99%